Caries in children with lactose intolerance and cow's milk protein allergy - Moimaz, Suzely Adas Saliba [UNESP]; Amaral, Marcelo Augusto [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Tânia Adas [UNESP]; Saliba, Orlando [UNESP] (FapUNIFESP (SciELO), 2018)
Dental caries in 5-to-8-year-old children with cow's milk protein allergy (CMPA) and lactose intolerance (LI), their treatment needs, and the consumption of milk-based products and milk derivatives by these patients were investigated. A cross-sectional study was undertaken with 200 children in southern Brazil in 2017. The clinical examination was based on the World Health Organization criteria and a questionnaire was sent to parents or legal guardians to collect information on the children's food intake, pre-existing systemic diseases, medication use, and CMPA and LI. Standardization was performed to verify concordance among examiners (kappa = 0.96). Caries prevalence was 67.50% in children with CMPA or LI, but 34.37% in those without these conditions. The mean dmft (decayed, missing, and filled teeth) index in children with CMPA or LI was 1.75 ± 1.84, significantly higher than among non-allergic or lactose-tolerant children (0.83 ± 1.60) (p < 0.001). In children with CMPA or LI, the mean for treatment needs was 1.58 ± 1.50. Lactose-free milk was the most frequently consumed food among allergic/intolerant children (65.00%), with a mean dmft of 2.00 ± 2.08, higher than that obtained for those without CMPA/LI (0.82 ± 0.87), showing no significant difference (p = 0.129). Although dental caries and treatment needs in primary dentition were associated with CMPA or LI, children's intake of replacement foods did not pose any risk for the development of carious lesions. Statistically significant differences were obtained for the prevalence and severity of dental caries. This shows the need for treatment of children with CMPA or LI, who had the worst caries prevalence and severity rates.